Práticas de escuta do rock: experiência estética, mediações e materialidades da comunicação - Jorge Luiz Cunha Cardoso Filho (2010)
This doctoral thesis deals with the comparative study of three listeningpractices developed through the interaction between listeners and threealbums of Rock bands, namely: Dark Side of the Moon (Pink Floyd),Nevermind (Nirvana) and In Rainbows (Radiohead). It presents adescriptive overview of the entering of the popular-massive musical model as a twentieth-century phenomenon, dependent on recording anddistribution technologies not previously seem the emergence of genreboundaries on Rock music, its dominant expressive shapes and associated cultural practices. It questions itself about the elements in play in the experience of each of the abovementioned albums, through the concepts of mediations and materialities, and it builds a methodological approach to apprehend the possibility conditions of experience grounded in material characteristics of the interactions, since the listening practices are made possible because of media issues. In conclusion, the comparative study reveals patterns of expression in Rock music, as the dependence of the album format; disruptions, such as the attentive listening disputing with the body and distracted listening, and privileges to specific mediations, residual or emerging ones. It also reveals broader issues to the study of aesthetic experience in the field of communication that can be employed in subsequent investigations.